Effect of Selected Metal Salts on the Microscopical Feature of Initial Carious - Like Lesion of Permanent Teeth (AN IN VITRO STUDY) (Mustansiria Dental Journal, 2018)
This study was designed to assess the microscopical changes of the enamel surfacebefore and following the treatment with different concentration of metal salts,involving zinc, strontium, magnesium, in addition to stannous fluoride and de-ionizedwater as the control.Microscopic examination was conducted on teeth samples before and followingpH-cycling procedure and following the treatment with the selected metal salt underpolarized microscope (100X).The best obvious remineralization was found following treatment with stannousfluoride, followed by zinc chloride. Samples treated with strontium chloride showedrather poorly mineralized surfaces. No signs of mineralization were observed forsamples treated with magnesium chloride.Although stannous fluoride was the best in the remineralization of initial caries,results for other metals seem to be promising if used for prevention of dental caries